Pediatric laparoscopic varicocelectomy using indocyanine green (ICG) fluorescence imaging - Keisuke Fukui; Takeshi Saito; Yasushi Fuchimoto (Elsevier, 2021)
In recent years, intraoperative ICG fluorescence has been used to evaluate blood flow and identify bile ducts. Moreover, varicocelectomy with intraoperative imaging using ICG has been reported; however, most of the reports have been on sparing lymphatics to prevent secondary hydrocele. Unlike conventional ICG imaging techniques, the PINPOINTⓇ system was able to display veins clearly and easily switch to color mode by simply pressing a button on the ICG at hand. In terms of simplicity, curability, and recurrence rate, the method of varicocelectomy remains controversial, such as microscopic, laparoscopic, total vascular ligation, or vein-only ligation. However, if recurrence rate is improved, considering the testicular atrophy caused by insufficient blood flow and the minimally invasive nature of the procedure, laparoscopic ligation of only the veins is ideal. We have successfully performed laparoscopic varicocelectomy by utilizing the characteristics of the PINPOINT® system and the intraoperative ICG fluorescence technique, sparing the arteries and lymphatics, and securely ligating and dissecting only the veins, including the surrounding venules. It is suggested that this technique can be used to perform pediatric laparoscopic varicocelectomy without increasing the recurrence rate compared to microscopic techniques.